Applicability of cement-stabilized municipal incinerated waste water sludge fly ash and lime-stabilized coal fly ash as lining/sub-based materials - Mahadevaswamy, M. et al. (2000)
Over the last decade the disposal of sludge has become a serious problem. Several investigations into the effective management of sludge have been made in the past. An experimental research programme was conducted to evaluate the potential of cement-stabilized municipal incinerated waste water sludge fly ash and lime-stabilized coal fly ash as lining materials, based on their physico-chemical and engineering properties. Leachate tests on the samples were carried out for inorganic constituents over a period of 42 days. Trace quantities of cadmium and chromium were detected which were within the drinking water limits. The above results indicate that the two mixtures can be used as liners for highway embankments. - Reproduced
Keywords: Sludge bulking; Waste water